Implementation of Environmental Education Value in Islamic Education (Analysis of Tafsir Al Qur'an Surah Al-A’raf Ayat 56-58) - Eka Yuni Purwanti (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
This research is based on the emergence of various problems of environmental damage caused by nature itself and humans. Environmental education is widely discussed in the Qur'an, one of which is in Surah Al-A’raf verses 56 to 58. Islamic education as an effective tool in conveying the importance of environmental education, so this study aims to determine the value of environmental education. life and implementation of environmental education in Islamic education. The research uses a qualitative approach with the type of library research and is analyzed using the content method. From this study, the results obtained from the letter Al-A’raf verses 56-58 on the interpretation of Al-Misbah written by M. Quraish Shihab about the value of environmental education, namely the environment is a facility given by Allah SWT to humans as provisions so that worship can be carried out properly. There is a prohibition against damaging the environment, whoever destroys it, the child will be punished in this world and in the hereafter, and will disturb the balance of the world's life. The obligation to preserve and protect the environment, a mandate from Allah SWT to protect nature is a responsibility that must be carried out. If people do good, they will get good results. And Surah Al-A’raf verses 56-58 on the interpretation of Al-Misbah written by M. Quraish Shihab can be implemented in Islamic education through character planting to form a Muslim personality, namely the environment is a facility given by Allah SWT. to humans, by instilling education and faith, knowledge, and self-awareness of the environment which is a mandate that must be maintained. There is a prohibition against damaging the environment and an obligation to preserve and protect the environment, both of these things through moral education, and worship education. Planting maintains and maintains the living environment properly and is based on maintaining the mandate of Allah SWT and later will return to Allah SWT so that it is worth worship and as gratitude for the pleasures given by Allah SWT.